The role of social movements in shaping the climate change knowledge and public discourse - Jamison, Andrew; Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2010)
The article is aimed at discussing the role of social movements in shaping the climate change knowledge and public discourse from the perspective of social movement theory, which has been relatively neglected in the scientific literature on climate change and knowledge. The article reviews relevant studies and theories of social movements with special attention to the role of knowledge making in social movements. It discusses the shaping and identity of social movements and relations between social movements and climate change knowledge from the 1970s to the present. The paper traces the emergence of climate change as an issue of public concern within the context of the environmental movements of the 1970s and 1980s. By contrast, paper argues that climate skepticism was shaped, in significant ways, by the neo-conservative and neo-nationalist movements that grew to political significance in the 1980s and 1990s. The neo-liberal movements of the 1990s and 2000s – albeit providing controversial views, food for public debates and narrowing the discourse to cost-benefit based approaches to climate change - are seen to have helped shaping the recent rise to public attention of climate change as an overarching political problem. In the concluding section, the article discusses how concerns with “climate justice” have emerged as part of a social movement for global justice, and contrasts the different social movements that have affected and influenced the making of climate change knowledge.